2022
DOI: 10.1002/slct.202200633
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Utilization of Mechanochemical and Microwave Methods for the Synthesis of Boc‐2‐amino‐quinazolin‐4(3H)‐ones and DFT Study of Mechanism 6π‐Diazaelectrocyclization Process

Abstract: Two eco‐friendly synthetic methods were used consecutively in the preparation of quinazolin‐4(3H)‐one heterocycles. The first reaction step, synthesis of a series of aryl guanidines was carried out by solvent‐free mechanochemical milling of aryl amines with 1H‐pyrazole‐N,N‐di‐(tert‐butyloxycarbonyl)‐1‐carboxamidine. In the following synthetic step, aryl guanidines were converted into Boc‐2‐amino‐quinazolin‐4(3H)‐ones by microwave heating. The experimental studies were supplemented by detailed quantum chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Here, we should note that the calculated barrier relates to the intramolecular proton transfer that involves the fourmembered cyclic TS structure which is known to be highly unfavorable. The elimination of methanol is a process that can be assisted by the external molecule(s) of water or the other proton-donating molecules which can significantly reduce the reaction barriers as shown by Antol et al [44]. Indeed, assuming the guanidine itself as the catalyst for the conversion of 15b_t1 to 17b_t1, the calculated barrier for the elimination of methanol was lowered from 88 kJ mol −1 to −72 kJ mol −1 (see Section S3 in the Supplementary Materials).…”
Section: Guandinesmentioning
confidence: 99%
“…Here, we should note that the calculated barrier relates to the intramolecular proton transfer that involves the fourmembered cyclic TS structure which is known to be highly unfavorable. The elimination of methanol is a process that can be assisted by the external molecule(s) of water or the other proton-donating molecules which can significantly reduce the reaction barriers as shown by Antol et al [44]. Indeed, assuming the guanidine itself as the catalyst for the conversion of 15b_t1 to 17b_t1, the calculated barrier for the elimination of methanol was lowered from 88 kJ mol −1 to −72 kJ mol −1 (see Section S3 in the Supplementary Materials).…”
Section: Guandinesmentioning
confidence: 99%
“…The N,N-Boc-protected N-amidinylpyrrole 28 [31] and 1-guanidinoanthracene (29) [10,32] have functional groups which were not tolerated under the debromination conditions and intractable mixtures of products were obtained. Carbomethoxypyrrole (30) was less susceptible to the reaction conditions, but unreactive.…”
Section: Scope Of the Reactionmentioning
confidence: 99%
“…Instead, small amounts of another cycloadduct were obtained. It was found that this is the product arising from anthraquinone (32), which was present as an impurity in 31. Independent milling of 10 with anthraquinone afforded dihydroxy cycloadduct 33 (in 35% yield) indicating that in the reaction conditions of the anthraquinone ↔ 9,10-dihydroxyanthracene (DHA) equilibrium is shifted towards DHA [34,35].…”
Section: Scope Of the Reactionmentioning
confidence: 99%